A potential role for shed soluble major histocompatibility class I molecules as modulators of neurite outgrowth. - Lorraine R Washburn; Dan Zekzer; Shoshana Eitan; Yuxin Lu; Hoa Dang; Blake Middleton; Christopher J Evans; Jide Tian; Daniel L Kaufman (PLoS ONE)
The neurobiological activities of classical major histocompatibility class I (MHCI) molecules are just beginning to be explored. To further examine MHCI's actions during the formation of neuronal connections, we cultured embryonic mouse retina explants a short distance from wildtype thalamic explants, or thalami from transgenic mice (termed "NSE-Db") whose neurons express higher levels of MHCI. While retina neurites extended to form connections with wildtype thalami, we were surprised to find that retina neurite outgrowth was very stunted in regions proximal to NSE-Db thalamic explants, suggesting that a diffusible factor from these thalami inhibited retina neurite outgrowth. It has been long known that MHCI-expressing cells release soluble forms of MHCI (sMHCI) due to the shedding of intact MHCI molecules, as well as the alternative exon splicing of its heavy chain or the action proteases which cleave off it's transmembrane anchor. We show that the diffusible inhibitory factor from the NSE-Db thalami is sMHCI. We also show that COS cells programmed to express murine MHCI release sMHCI that inhibits neurite outgrowth from nearby neurons in vitro. The neuroinhibitory effect of sMHCI could be blocked by lowering cAMP levels, suggesting that the neuronal MHCI receptor's signaling mechanism involves a cyclic nucleotide-dependent pathway. Our results suggest that MHCI may not only have neurobiological activity in its membrane-bound form, it may also influence local neurons as a soluble molecule. We discuss the involvement of complement proteins in generating sMHCI and new theoretical models of MHCI's biological activities in the nervous system.